2014
DOI: 10.1002/aic.14397
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten hexacarbonyl and hydrogen peroxide as precursors for the growth of tungsten oxide thin films on titania nanoparticles

Abstract: W(CO) 6 and H 2 O 2 were used in an atomic layer deposition (ALD)-like process to grow thin WO x films onto TiO 2 powders in a fluidized bed reactor. Carbonyl precursors are not widely used in this application, so that deviations from an ideal ALD process, previously not examined with W(CO) 6 , were identified. The resulting WO x films were a result of both ALD-like and chemical vapor deposition-based growth modes. A chemical reaction mechanism incorporating a combination of these two growth modes was inferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…Unfortunately, more details were not provided for this ALD process. The ALD process of WO 3 using W(CO) 6 / H 2 O 2 was investigated by Jackson et al 212 In the range of 180-200 C, they found that the precursor pair of W(CO) 6 /H 2 O 2 could not achieve a pure form of ALD growth, but continuous dosing of W(CO) 6 could always increase the growth rates. They also noticed that W(CO) 6 was prone to decompose even at a temperature of 80 C, and this explained the continuous unsaturated growth of WO 3 with extended dosing of W(CO) 6 .…”
Section: Layered Transition Metal Oxides Moomentioning
confidence: 99%
“…Unfortunately, more details were not provided for this ALD process. The ALD process of WO 3 using W(CO) 6 / H 2 O 2 was investigated by Jackson et al 212 In the range of 180-200 C, they found that the precursor pair of W(CO) 6 /H 2 O 2 could not achieve a pure form of ALD growth, but continuous dosing of W(CO) 6 could always increase the growth rates. They also noticed that W(CO) 6 was prone to decompose even at a temperature of 80 C, and this explained the continuous unsaturated growth of WO 3 with extended dosing of W(CO) 6 .…”
Section: Layered Transition Metal Oxides Moomentioning
confidence: 99%
“…Tungsten hexacarbonyl W(CO) 6 is one of the most used precursors. [196][197][198][199][200] Using ozone as oxygen source, narrow ALD window between 195 and 205°C with a GPC of 0.2 Å/cycle is noted. 196,197 While Nandi and Sarkar 196 report amorphous films that could be converted to monoclinic WO 3 upon annealing, Malm et al 197 obtain partially crystallized as-deposited films that can considerably be improved by annealing at 600-1000°C under oxygen or nitrogen atmospheres.…”
Section: Tungsten Oxidementioning
confidence: 99%
“…On the other hand, from H 2 O 2 and W(CO) 6 , thin WO x films are successfully grown onto TiO 2 particles using a fluidized bed reactor. 198 The WO x films result from both ALD-like and CVD-based growth modes, the determined W/Ti atomic ratio being partially dependent on the tungsten and oxygen precursor pulse lengths.…”
Section: Tungsten Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…However, this claim is somewhat controversial because it is generally accepted that a full Al2O3 monolayer (0.38 nm) can only be obtained after 3-4 ALD cycles (George, 2010). Similarly, for a material with a low growth-per-cycle (GPC), WOx, a film of 0.46 nm was measured by TEM after 25 cycles of W(CO)6 and H2O2 on commercial Degussa P25 TiO2 nanoparticles (Jackson, Dunn, Guan, & Kuech, 2014). To our knowledge, the thickest ALD film grown on a powder support is a ~110 nm Al2O3 passivation barrier deposited onto Fe powder particles (Moghtaderi, Shames, & Doroodchi, 2006).…”
Section: Ald Nanostructuringmentioning
confidence: 99%